1996
DOI: 10.1144/gsjgs.153.6.0915
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP constraints on sediment provenance and transport history in the Mesozoic Statfjord Formation, North Sea

Abstract: Detrital zircons in sandstones of the Statfjord Formation (late Triassic-early Jurassic) in the northern North Sea have been dated with the sensitive high resolution ion microprobe (SHRIMP). These sandstones lack detailed biostratigraphic control, but display distinct variations in heavy mineral assemblages which facilitate a three-fold subdivision of the sequence. The lower and middle zones (heavy mineral Zones A and B) have similar characteristics, both displaying a marked upward decline in garnet abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 15 publications
0
15
0
3
Order By: Relevance
“…Analysis of dense minerals is widely used as a tool for stratigraphic correlation in sandstone dominated sequences lacking biostratigraphic control (Weissbrod and Nachmias 1986, Morton 1991, Morton and Hurst 1995, Mange-Rajetzky 1995, Smaler and Laird 1995, Morton et al 1996, Morton and Grant 1998, Hermann and Polozek 1999, Svendsen and Hartley 2002, Mange et al 2003. Other studies focusing sedimentary basins in northern and northeastern Brazil have shown that this type of approach using heavy minerals might be of a valuable tool for helping to establish the stratigraphic framework in areas where the sedimentary units display similar lithofaciological composition (Rossetti et al 1989, Sousa et al 2000, Nascimento and Góes 2005, Truckenbrodt et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of dense minerals is widely used as a tool for stratigraphic correlation in sandstone dominated sequences lacking biostratigraphic control (Weissbrod and Nachmias 1986, Morton 1991, Morton and Hurst 1995, Mange-Rajetzky 1995, Smaler and Laird 1995, Morton et al 1996, Morton and Grant 1998, Hermann and Polozek 1999, Svendsen and Hartley 2002, Mange et al 2003. Other studies focusing sedimentary basins in northern and northeastern Brazil have shown that this type of approach using heavy minerals might be of a valuable tool for helping to establish the stratigraphic framework in areas where the sedimentary units display similar lithofaciological composition (Rossetti et al 1989, Sousa et al 2000, Nascimento and Góes 2005, Truckenbrodt et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Results with more than 10% discordant were not considered in the probability plots. The number of analyzed grains is under the minimum recommended (Morton et al, 1996). Therefore, the interpretations were made under restrictions, since the data can be biased.…”
Section: Sampling and Methodsmentioning
confidence: 99%
“…12). The simultaneous changes in GZi and ATi values indicate that the packages of low GZi and ATi represent relatively intensively chemically weathered horizons, most likely prior to deposition (Morton & Berge 1995;Morton et al 1996). If the decrease in the GZi values was because of intrastratal dissolution of garnet during burial, then the ATi would remain unaffected, as apatite and tourmaline are both ultrastable during burial (Morton 1986;Morton & Hallsworth 2007).…”
Section: Heavy Minerals: a Tool For Stratigraphic Correlationmentioning
confidence: 99%